KAJIAN TEOLOGIS UNGKAPAN ”CELAKALAH AKU JIKA AKU TIDAK MEMBERITAKAN INJIL” DALAM 1 KORINTUS 9:16B - Pranoto, David Susilo (Manna Rafflesia, 2018)
Individualism increasingly affects human life. This makes people busy with their respective activities. Facing such conditions, how is the urgency of evangelism today. Therefore to answer that principle, we need to understand Paul's expression which is: "woe to me if I do not preach the gospel". Through this article can help believers realize their role in the world today.